Performance appraisal as a correlate of employees’ productivity in Osun state, Nigeria - Oniyide, Adekunle Oyebola; Odeyemi, Olusola Olatunbosun (Management and Entrepreneurship: Trends of Development, 2024)
The study explored performance appraisal as a correlate of employees’ productivity in Osun State, Nigeria. Specifically, the study investigated the effect of performance appraisal feedback, performance appraisal rewards, performance appraisal training and performance appraisal methods on the employees’ productivity. The study employed the use of descriptive statistics of frequency distribution, percentages and inferential statistics of Ordinary Least Square (OLS) regression analysis to determine the effects of identified four (4) performance appraisal systems on employees’ productivity in the area of study. The results of the analysis revealed that both performance appraisal feedback and rewards systems have positive but insignificant impacts on employees’ productivity while both performance appraisal-based training and methods systems exerted positive and noticeable significant impacts on employees’ productivity in the study area. The study therefore concluded that performance appraisal feedback and rewards system have positive but insignificant impact on employees’ productivity while both performance appraisal-based training and method systems exerted positive and noticeable significant impacts on employees’ productivity.JEL Classification: J40, J42, J22